Supraspinatus Muscle Tendon Lesion and Its Relationship with Long Head of the Biceps Lesion - Cassiano Diniz Carvalho; Carina Cohen; Paulo Santoro Belangero; Alberto de Castro Pochini; Carlos Vicente Andreoli; Benno Ejnisman (Revista Brasileira de Ortopedia)
Abstract Objective To identify the clinical, radiological, and arthroscopic correlation of long head of the biceps tendon injuries and their influence on pain when associated with rotator cuff injuries. Methods Between April and December 2013, 50 patients were evaluated, including 38 (76%) women and 12 (24%) men, with a mean age of 65.1 years old. The patients were operated by the Shoulder and Elbow Group, Discipline of Sports Medicine, Orthopedics and Traumatology Department, Universidade Federal de São Paulo. The subjects underwent repair of the rotator cuff lesion with clinical, radiological and/or arthroscopic evidence of involvement of the long head of the biceps tendon. Results An association between pain at palpation of the intertubercular groove of the humerus and high-grade partial lesions (partial rupture of the tendon affecting more than 50% of its structure) was observed at the arthroscopy (p = 0.003). There was also an association between the high-grade lesion of the long head of the biceps and injury to the supraspinatus muscle tendon (p < 0.05). For each centimeter of the supraspinatus muscle tendon injury, the patient presented a 1.7 higher probability of having a high-grade lesion at the long head of the biceps. Conclusion Pain at the anterior shoulder region during palpation of the intertubercular groove of the humerus may be related to high-grade lesions to the long head of the biceps. Rotator cuff injury and its size are risk factors for high-grade injuries to the long head of the biceps tendon.